The Characteristics of the Cases which Admitted to Emergency Department of Trakya University Medical Faculty - Altun, Gürcan; Azmak, Ali Derya; Yılmaz, Ahmet; Yılmaz, Gözde (The Bulletin of Legal Medicine, 1997)
2802 cases were admitted to Emergency Department of Trakya University Hospital between September 1992 and September 1995. 2196 (78%) were male, 606 (22 %) were female. The average age was 30.52 (+15.15). It was noted that the frequency of legal cases which admitted to hospital increased between June and August. 102 cases were dead on arrival (DOA) at the hospital whereas 32 cases died in the emergency department during their treatment. Traffic accident was the leading cause with 1762 cases (62.9 %). This was followed by 282 cases of assault, and falls and falls from height with 175 cases. While traumatic lesions were seen in more than one body region in 853 cases (33 %), head and neck injuries were seen in 785 cases (29 %). 1817 cases were treated in the emergency department as outclinic patients, and 883 cases were admitted as patients to the hospital. It was observed that 433 cases were under the influence of alcohol. In 1362 (50 %) cases, there was no any information about alcohol. Similarly there w-ere life threatening injuries in 432 cases, whereas there was no medical documentation which showed that whether injuries were life threatening or not. The aim of this study was to reveal insufficient medical documentation after determining of the epidemiological characteristics of legal cases. Key words: Emergency department, forensic cases, trauma, alcohol, injuries.